Study protocol for a pilot quasi-experimental study on oral health education for nurses and community health workers in Nigeria - Oladayo, Abimbola M.; Lawal, Folake B.; Sofola, Oyinkansola O.; Uti, Omolara G.; Oyapero, Afolabi; Aborisade, Adetayo; Stewart, Bernal; Daep, Carlo Amorin; Hines, Deon; Beard, Jacinto; Dedeke, Aderonke; Fagbule, Omotayo F.; et al. (Frontiers in Public Health, 2024)
Introduction The primary health care system provides an ideal setting for the integration of oral health into general health care as well as equitable access to oral health care. However, the limited oral health knowledge of primary health care workers necessitates appropriate training before they can participate in health promotion efforts. This pilot training was designed to examine the impact of the Oral Health Education module for Nurses and Community Health Care Workers on their oral health awareness and referral practices. Methods This study will utilize a quasi-experimental design (pre-and post with a non-equivalent control group) to assess the impact of a five-day pilot oral health education program on the knowledge and referral practices of Nurses and Community Health Workers in primary health care centers in three states in Nigeria-(Lagos, Oyo, and Kano). The training modules were developed based on the six iterative steps described in the intervention mapping framework – needs assessment, highlighting program objectives and outcomes, selection of theory and mode of intervention, designing program based on theory, designing implementation plans, and developing an evaluation plan. Only the intervention group will participate in the full educational training sessions but both groups will complete the pre-and post-intervention questionnaires. Discussion This pilot training combined the standardized training modules from the recently launched “Oral Health Training Course for Community Health Workers in Africa” and a newly developed maternal and child oral health module by our group using an evidence-based approach. To the best of our knowledge, this is the first program to examine the impact of the standardized OpenWHO modules. The success of this training will lay the foundation for developing a sustained channel for providing oral health education at the primary health care level in Nigeria, West Africa, and Africa.